Mometasone furoate effect on interleukin-6 of adenoid surface and serum in adenoid hypertrophy patients - Zainul Mujahid; Rus Suheryanto; Iriana Maharani (Oto Rhino Laryngologica Indonesiana, 2021)
Background: Adenoid hypertrophy is one of the most common problems in children resulting in obstruction of the posterior nasal cavity. Interleukin-6 (IL-6) is a pleiotropic cytokine that plays a role in acute and chronic infections, hematopoesis, T cells and B cells formation. Purpose: To determine the effect of intranasal mometasone furoate administration on IL-6 level of adenoid surface and serum and the adenoid size in patients with adenoid hypertrophy. Method: A one group pre- and post-test design involving 17 patients aged 5 to 12 years. The subjects underwent nasoendoscopic examination to determine the adenoid size, also measurement of IL-6 level of adenoid surface and serum before and after 6 weeks treatment with intranasal mometasone furoate. Results: There were a significant decrease of the adenoid surface IL-6 level, serum IL-6 level, and adenoid size with p value <0.05. There was a significant positive correlation between the levels of adenoid surface IL-6 and serum IL-6 (r=0.517; p=0.033). A significant positive correlation was obtained between the decrease of adenoid surface and serum IL-6 levels with the decrease of adenoid size (p<0.05). Conclusion: The use of intranasal mometasone furoate could decrease the IL-6 levels of adenoid surface and serum, and the adenoid size in patients with adenoid hypertrophy.ABSTRAK Latar belakang: Hipertrofi adenoid merupakan salah satu masalah tersering pada anak-anak yang mengakibatkan obstruksi pada rongga hidung posterior. Interleukin-6 merupakan sitokin pleiotropik yang berperan pada infeksi akut maupun kronis, hematopoesis, pembentukan sel T dan sel B. Tujuan: Mengetahui pengaruh pemberian mometason furoat intranasal terhadap kadar IL-6 permukaan adenoid dan serum, serta ukuran adenoid pada penderita hipertrofi adenoid. Metode: Suatu one group pre- and post-test design melibatkan 17 subjek berusia 5 sampai 12 tahun. Subjek menjalani pemeriksaan nasoendoskopi, pengukuran kadar IL-6 serum, dan IL-6 permukaan adenoid sebelum dan setelah pemakaian mometason furoat intranasal selama 6 minggu. Hasil: Didapatkan penurunan kadar IL-6 permukaan adenoid, IL-6 serum, dan penurunan ukuran adenoid yang bermakna dengan nilai p<0,05. Didapatkan korelasi positif yang signifikan antara kadar IL-6 permukaan adenoid dengan IL-6 serum (r=0,517; p=0,033). Didapatkan korelasi positif yang signifikan antara penurunan kadar IL-6 permukaan adenoid dan IL-6 serum dengan pengecilan ukuran adenoid (p<0,05). Kesimpulan: Penggunaan mometason furoat intranasal dapat menurunkan kadar IL-6 permukaan adenoid dan IL-6 serum, serta ukuran adenoid pada penderita hipertrofi adenoid. Kata kunci: hipertrofi adenoid, interleukin-6, mometason furoat intranasal